A phytoextraction trial strengthened by Streptomyces pactum and plant nutrients: In view of plant bioindicators and phytoextraction indices. (October 2020) - Guo, Di; Ren, Chunyan; Ali, Amjad; Zhang, Yang; Du, Juan; Wang, Ping; Li, Ronghua; Zhang, Zengqiang
Abstract: The present work was done to explore the joint effect of Streptomyces pactum (Act12) and plant nutrients on phytoremediation of smelter-contaminated soils. The physiological indicators and phytoextraction indices of potherb mustard ( Brassica juncea, Coss ) grown in Act12 inoculated soil with or without Hoagland's solution (H), humic acid (HA) and peat (PS) were evaluated. The results indicated that H, HA and PS acted synergistically with Act12, notably increasing chlorophyll and soluble protein contents and thereby promoting plant growth. Soil nutrient treatments reduced the antioxidant activities (PPO, CAT and POD) by 28.2–41.4%, 22.3–90.1% and 15.2–59.4% compared to control, respectively. Act12 and H treatments markedly facilitated plant to accumulate more cadmium (Cd) and zinc (Zn), but it was observed decreases when applied with HA and PS. Metal uptake (MU) values further indicated the differences in phytoextraction efficiency, i.e., H > PS > Control > HA. Taken together, Act12 combined with plant nutrients contributed to alleviating metal toxicity symptoms of plant. Hoagland's solution and peat were highlighted in the present phytoextraction trial, and recommended as soil additives. Graphical abstract: Image 1 Highlights: The effect of strain and plant nutrients on the phytoextraction was evaluated. Potherb mustard growth was promoted after strain and nutrient treatments. Plant mediates enzymatic activities to resist the stress of Cd and Zn. The phytoextraction efficiency followed Hoagland's solution > peat > humic acid. Abstract : The assisted phytoextraction efficiency followed Hoagland's solution > peat > humic acid.